Reduction of Coenzyme Q10 Content: A Possible Effect of Isoproterenol on Heart Failure and Myocardial Infarction in Rat - Khorrami, A.; Garjani, A.; Ghanbarzadeh, S.; Andalib, S. (Drug Research, 2014)
Myocardial infarction (MI) was induced by subcutaneous injection of isoproterenol (ISO) to investigate the effect of ISO on Coenzyme Q10 (CoQ10) content of myocardium and subsequent effects on lipid peroxidation, electrocardiogram pattern and hemodynamic parameters of the rat’s heart.36 male Wistar rats were divided randomly into 6 groups. To induce heart failure (HF) and MI, 10 and 100 mg/kg of ISO was administered subcutaneously for 10 and 2 consecutive days, respectively. The effects of ISO on myocardium CoQ10 content, concentration of malondialdehyde, ECG pattern and hemodynamic parameters of heart were analyzed.ISO-treated rats showed significant alteration in heart hemodynamic parameters such as reduction of left-ventricular systolic pressure, maximum and minimum rate of developed left ventricular pressure, besides increase of left ventricular end-diastolic pressure. Significant depletion of heart CoQ10 content (from 4.57 and 4.55 µg/100 mg tissue in control groups to 2.85 and 2.89 µg/100 mg tissue in ISO-induced HF and MI groups respectively) and increase in tissue levels of malondialdehyde (47.1 and 53.8 nmol/100 mg tissue in ISO-induced HF and MI groups, respectively) were also observed in ISO-treated animals compared with the normal animals (17.4 and 18.8 nmol/100 mg tissue in control groups, respectively). Additionally CoQ10 improved ISO effects on hemodynamic parameters and ECG pattern in ISO-induced HF and myocardial injury.The present findings have demonstrated that the cardiotoxic effects of ISO such as oxidative damage and hemodynamic declination might be related to depletion of CoQ10 concentration.
Keywords: CoQ10; isoproterenol; myocardial infarction; heart failure